Watching the universe - Gribbin, John (Hyderabad, Universities Press (India)Limited, 1998)
How would the dinosaurs have evolved if they hadn't been wiped out by a giant meteorite 65 million years ago? Is most of the universe in the form of mysterious 'dark matter' that we cannot see ? How does the sun shine? Can mass be spewed into the universe from white holes- like black holes in reverse? What do supernovae mean to us? In a series of essays collected together for the first time........
Index 225-234p.
Keywords: Astronomy